Do common genotypes of FK506 binding protein 5 (FKBP5) moderate the effects of childhood maltreatment on cognition in schizophrenia and healthy controls?. (November 2015) - Green, Melissa J.; Raudino, Alessandra; Cairns, Murray J.; Wu, Jingqin; Tooney, Paul A.; Scott, Rodney J.; Carr, Vaughan J.; ,
Abstract: Common variants of the FK506 binding protein 5 ( FKBP5 ) gene are implicated in psychotic and other disorders, via their role in regulating glucocorticoid receptor (GR) receptor sensitivity and effects on the broader function of the HPA system in response to stress. In this study, the effects of four FKBP5 polymorphisms (rs1360780, rs9470080, rs4713902, rs9394309) on IQ and eight other cognitive domains were examined in the context of exposure to childhood maltreatment in 444 cases with schizophrenia and 292 healthy controls (from a total sample of 617 cases and 659 controls obtained from the Australian Schizophrenia Research Bank; ASRB). Participants subjected to any kind of maltreatment (including physical, emotional, or sexual abuse or physical or emotional neglect) in childhood were classified as 'exposed'; cognitive functioning was measured with Repeatable Battery for the Assessment of Neuropsychological Status, the Controlled Oral Word Association Test, and IQ was estimated with the Weschler Test of Adult Reading. Hierarchical regressions were used to test the main effects of genotype and childhood maltreatment, and their additive interactive effects, on cognitive function. For rs1360870, there were significant main effects of genotype and childhood maltreatment, and a significant interaction of genotype with childhood trauma affecting attention in both schizophrenia and healthy participants (C-homozygotes in both groups showed worse attention in the context of maltreatment); in SZ, this SNP also affected global neuropsychological function regardless of exposure to childhood trauma, with T-homozygotes showing worse cognition than other genotypes. The mechanisms of trauma-dependent effects of FKBP5 following early life trauma deserve further exploration in healthy and psychotic samples, in the context of epigenetic effects and perhaps epistasis with other genes. Study of these processes may be particularly informative in subgroups exposed to various other forms of early life adversity (i.e., birth complications, immigration). Graphical abstract: Interactive effects of FKBP5 SNP rs1360780 and childhood trauma exposure on attention in schizophrenia (A) and Healthy Controls (B). Highlights: Individuals homozygous for the major allele (C) of FKBP5 rs1360780 show worse attention in the context of maltreatment, regardless of case-control status. Variation in rs1360780 contributes also to general neuropsychological ability in SZ regardless of exposure to childhood trauma. IQ levels in healthy controls were influenced by variation in rs4713902 interacting with childhood maltreatment.